PENGELOLAAN PEER TEACHING BERBANTUKAN GADGET DALAM MENURUNKAN STRES BELAJAR SISWA DI MASA PANDEMI - Zakiyah BZ (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
This study aims to find out the effectiveness of peer teaching methods through Gadged in lowering student stress levels during pandemics. The subjects of this study were 40 students who had learning stress problems. Of the 40 study subjects divided into two groups, namely, 20 experimental groups and 20 control groups. The measuring instrument used in this study is a questionnaire data with student learning stress indicators in the form of 32 statement items to determine the level of learning stress experienced by students. The questionnaire is used as a pre test and post test. Data analysis techniques used are independent techniques of sample t-test using SPSS 16 program. Based on the results of research and discussion about learning stress in students, after being treated with peer teaching method through gadgets showed that the results of the 3rd output (Paired Samples Test) on learning stress variables, obtained Sig value. (2-tailed) = 0.01 in the experiment group and 0.0400 in the control group smaller than 0.05 (0.000 0.05). So it can be concluded that Ha was accepted and H0 rejected.